Limited attention and status quo bias - Mark Dean; Özgür Kibris; Yusufcan Masatlioglu (Brown University, Department of Economics, 2014)
We introduce and axiomatically characterize a model of status quo bias in which the status quo affects choices by both changing preferences and focusing attention. The resulting Limited Attention Status Quo Bias model can explain both the finding that status quo bias is more prevalent in larger choice sets and that the introduction of a status quo can change choices between non-status quo alternatives. Existing models of status quo bias are inconsistent with the former finding while models of decision avoidance are inconsistent with the latter. We report the results of laboratory experiments which show that both attention and preference channels are necessary to explain the impact of status quo on choice.
Keywords: D03; D83; 330; Status Quo Bias; Reference Dependence; Attention; Revealed Preference